Implementation of the Independent Curriculum to Improve the Quality of Learning English - Syahfitri Purnama; Pawiro, Muhammad Ali (Universitas Pendidikan Ganesha, 2023)
This independent curriculum introduces a new framework for students centered on Merdeka learning models, with the goal of fostering their self-assurance and ingenuity. School educators design English teaching plans while guiding students through project-based learning initiatives until they achieve proficiency and commendable performance by the end of the semester. Considering that English stands as a global language, students must attain mastery to prevent lagging behind other nations in the era of globalization. This research aims to analyze the application of the Merdeka Curriculum in improving the quality of learning, especially English, and whether this approach can strengthen creativity and English language proficiency among educators and students. By employing a qualitative methodology utilizing content analysis, the study relies on data derived from questionnaires distributed to 158 English teachers and interviews conducted with educators situated. The examination of the findings reveals that 77.2% of English teachers acknowledge the presence of an independent curriculum, and 76.6% of students have experienced improvements in skills and creativity. For the continuous implementation of the Merdeka curriculum, educators should further enhance their knowledge, take a proactive role in encouraging and assisting students both within and beyond the classroom settings, and design English learning projects that foster the development of students aligned with the Pancasila principles, capable of thriving in the future competitive landscape.